The Impact of Income, Interest, and Financial Literacy on Sharia Banking Products in Semarang City: A Moderating Effect of Religion - Purnomo, Hadi; Prabantarikso , Mahelan (UPT Publikasi Ilmiah UNISBA, 2025)
This study found that income, financial literacy, and religiosity significantly influence the use of Islamic banking products in Semarang, with the research conducted from February to March 2024, while interest did not have a significant impact. This study, involving 85 respondents, used the PLS-SEM method and tested seven hypotheses, with five yielding positive results. The research highlights the interaction between economic, social, and religious factors in Islamic banking. Practically, Islamic banks are advised to strengthen financial literacy based on religious values and tailor their products to match customers' income profiles and religiosity.